Pengaruh Circuit Training Terhadap Motivasi Santri Putra Dalam Melaksanakan Aktivitas Olahraga di Pondok Pesantren Nurul Jadid - Khoirul Mawahib; Catur Supriyanto; Made Pramono; Fatkur Rohman Kafrawi (STIKes Ibnu Sina Ajibarang, 2024)
Sport for all is a movement that emerged to bring awareness to the importance of sport for all. This movement is based on the community's need for sports regardless of all kinds of differences, including for someone who is in an Islamic boarding school environment. This research aims to determine the effect of Circuit Training exercises on students' motivation in carrying out sports activities at the Nurul Jadid Islamic Boarding School, Probolinggo. The method used in this research is a quasi-experiment or quasi-experiment with a one group Pretest and Posttest Design research design. In this research, the number of samples used was 15 respondents using a purposive sampling technique or determining certain criteria. The instrument in this research uses a questionnaire. Then the data that has been obtained and collected will be analyzed using descriptive tests with the help of the SPSS VERSION 25 application program. Next, the data will be tested using the Kolmogorov-Smirnov normality test, this test is used to find out whether the data obtained in the research is normally distributed or not. Then, to test the hypothesis, use the T Paired Sample Test to determine the effect of providing treatment in each treatment group. After analyzing the research data. The results of the research show that there is a significant influence on Circuit Training exercises on students' motivation in carrying out sports activities at the Nurul Jadid Islamic Boarding School, Probolinggo.